Analisis Framing Pemberitaan Izin Proyek Meikarta pada Media Online CNN Indonesia.com dan Kompas.com Edisi Agustus-September 2017 (Faculty of Communications Science, Dr. Soetomo University, 2018)
The purpose of this study was to find out how to frame kompas.com and cnnindonesia.com in framing the news about the issue of the Meikarta project. Framing analysis using the Pan and Kosicki models. The framing results found a tendency for cnnindonesia.com members to benefit, and the positive side. Kompas.com still reports on Amdal and licensing, but also keeps giving a portion of news about promotions and benefits of Meikarta. Keywords: framing analysis, online media, meikarta.